Lifestyle Mobilities: A Politics of Lifestyle Rock Climbing. (14th March 2016) - Rickly, Jillian M.
Abstract: The conceptualization of 'lifestyle mobilities' has yet to fully account for the diversity within and across mobile communities in terms of leisure, travel, and identity. Lifestyle rock climbers, for example, maintain minimalist, hypermobile lifestyles in the full-time, non-professional pursuit of the sport. In an effort to interrogate lifestyle rock climbing within the broader conceptualization of lifestyle mobilities, this paper applies mesotheoretical 'politics of mobility' framework. It begins by tracing constellations of mobility and historical contexts within the rock climbing community more broadly. This is followed by an examination of the facets of a politics of mobility: motive force, speed, rhythm, route, experience, friction, turbulence, and remove, which together offer more nuanced understandings of the movement patterns and travel decisions of lifestyle climbing. However, to account for the community dynamics of lifestyle mobilities, there is a need to delve deeper and attend to the social relations that result from collective performances.